Numerical Solution of Dual Fully Fuzzy Equations System Using Some Meta Heuristic Methods - Aang Nuryaman; Fatimatuzzahra; Rafiq Arssy Arifa; La Zakaria; Muhammad Ahsar Karim (International Journal of Mathematical, Engineering and Management Sciences)
Nowadays, there is more and more attention from researchers in solving various problems in the applied field of fuzzy equations, one of which is the fluid mechanics problem of reservoir piping. In this article, we investigate a solution to a dual fully fuzzy equations system involving triangular and trapezoidal fuzzy numbers using a numerical approach, especially meta-heuristic methods. We consider the equations system in crisp equations form as an optimization problem, and then its problems are solved. Here we compare the performance of four meta-heuristic methods, i.e., genetic algorithm (GA), chaos optimization algorithm (COA), particle swarm optimization (PSO), and grey wolf optimizer (GWO), to solve some cases in our problems. The results obtained show that PSO gives performance that is better than of other methods. Furthermore, the type of initial population number in GA affects how close the numerical solutions are to the exact solution.